American assassin : a thriller - Flynn, Vince (New York : Pocket Books, 2011)
Follow Mitch Rapp, as he takes on his first explosive counter-terrorism assignment.
Keywords: Rapp, Mitch (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Intelligence officers -- Fiction; Suspense fiction